THE CONCEPT OF DEATH. FROM SOCRATES TO ELLIS - BUMBAȘ, Aurel; VAIDA, Sebastian (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2020)
Death is a concept studied from ancient times by all major areas, from literature and art, to philosophy and psychology. In this research, we analyze the way Socrates, the famous Greek philosopher, negotiates the idea of death, through his own death. We approached this, because the ancient philosopher was put in this situation when he was sentenced to death, unjustly, following a democratic decision. His way of seeing death reveals a formula that does not match the expectation of his contemporaries, nor the classical typology of the imminence of his own death, belonging to psychiatrist Elizabeth Kübler-Ross. And the explanation of this non-coincidence is based on the philosophical idea of man and world and the specifics of his philosophical practice. It is precisely this philosophical conception and practice that will make Socrates’ attitude become repeatable and not unrepeatable, as one might expect, since this attitude appears so conditioned by specific elements. In fact, the rational research on the grounds of beliefs and personal knowledge that stands at the basis of his philosophical practice, is deeply rooted in the foundations of Rational Emotive Behavior Therapy (REBT). Therefore, what lays at the basis of Socrates’ view on death goes far beyond the ancient cultural framework. To fill in the phenomenal dimension with the one of organic layer, the analysis will also include an interpretation of Socrates’ behavior, from the dopamine mechanism approach.